Mind the (gender pay) gap: the role of board gender composition - Yannis Galanakis; Amanda Gosling (Journal of Population Economics, 2026)
We study how the share of female directors affects company-reported gender pay gaps using linked administrative data. We combine gender pay gap reports with proprietary board-composition data for 8,411 UK firms with at least 250 employees (2017–2021). Our identification uses a Bartik (1991)-style instrumental variable design that exploits regional shifts in female board representation. A one-percentage-point increase in the female director share reduces the gender pay gap by 0.043 percentage points. Moving from the current UK average to board gender parity would close about one-sixth of the reported 9.7% pay gap. The effect operates through three channels. Female directors generate asymmetric wage increases favouring women, improve female representation across pay quartiles, and ensure more equitable allocation of performance-related pay. Effects are concentrated in firms with 250-5,000 employees and are strongest when UK nationals comprise a board majority.
Keywords: C26; G30; G34; J16; J31; L16; 330; Board of directors; Women on boards; Gender pay gap